Role Stress, Supervisor Support and Burnout in Local Government Internal Auditors - Agil Novriansa; Aryanto Aryanto; Burhanuddin Burhanuddin; Mega Aulia Putri; Renaldi Setiawan (Faculty of Economics, Universitas Sriwijaya, 2021)
This study aims to empirically examine the relationship between role stress and supervisor support with burnout on local government internal auditors. Sampling was carried out by purposive sampling method with criteria in the form of local government internal auditors who had at least one year of audit experience. The results of an online survey on the auditors of the Regency/City Government Inspectorate in Southern Sumatera Province were obtained as many as 155 respondents who participated as samples of this study. The results of data analysis using SEM-PLS show that role conflict is not associated with emotional exhaustion and reduced personal accomplishment, but is positively associated with depersonalization. Role ambiguity is positively associated with emotional exhaustion and reduced personal accomplishments, but role ambiguity is negatively associated with depersonalization. Role overload is positively associated with emotional exhaustion and depersonalization but negatively associated with reduced personal accomplishment. Supervisor support is negatively associated with all burnout dimensions.